2010
DOI: 10.1111/j.1532-5415.2010.02763.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Relationship Between Age and the Effect of Risedronate Treatment in Women with Postmenopausal Osteoporosis: A Pooled Analysis of Four Studies

Abstract: OBJECTIVES:To quantify the effect of age on the incidence of osteoporosis-related fractures and of risedronate treatment on fracture risk in different age groups in women with postmenopausal osteoporosis. DESIGN: Data from four randomized, double-blind, placebo-controlled, Phase III studies were pooled and analyzed. PARTICIPANTS: The analysis population (N 5 3,229) consisted of postmenopausal women with osteoporosis as determined on the basis of prevalent vertebral fractures, low bone mineral density (BMD), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The upper tertile for age extends from 73 to 91 years at baseline and from 79 years upwards at trial‐end. Fracture prevention is still apparent in this group, addressing an ongoing concern that efficacy of osteoporosis treatments has not been clearly demonstrated in elderly women . This study did not provide calcium supplements to participants, yet still demonstrated anti‐fracture efficacy in their absence.…”
Section: Discussionmentioning
confidence: 99%
“…The upper tertile for age extends from 73 to 91 years at baseline and from 79 years upwards at trial‐end. Fracture prevention is still apparent in this group, addressing an ongoing concern that efficacy of osteoporosis treatments has not been clearly demonstrated in elderly women . This study did not provide calcium supplements to participants, yet still demonstrated anti‐fracture efficacy in their absence.…”
Section: Discussionmentioning
confidence: 99%
“…In bisphosphonate fracture trials, subgroup analyses have consistently demonstrated efficacy among the oldest individuals [39][40][41] and those with neurologic impairment, 42,43 though these estimates were imprecise and not directly representative of frail adults or NH residents. In the Fracture Intervention Trial comparing alendronate vs placebo among 3658 community-dwelling postmenopausal women, the NNT was 189 over 2 years of follow-up in the oldest subgroup (patients aged 75-85 years), which is similar to our 3-year estimate of 239.…”
Section: Discussionmentioning
confidence: 99%
“…For risedronate, there was a significant 44 % reduction in the risk of vertebral fractures (relative to placebo) in women aged 80 years or above but no significant difference in the incidence of nonvertebral fractures [15]. A pooled analysis of RCTs in postmenopausal women with osteoporosis found that, despite a 4 % increase in the risk of fracture for every 1-year increase in age, there was a 46 % reduction in the risk of clinical fracture over 3 years with risedronate treatment [17]. For zoledronic acid, post hoc subgroup analysis of pooled data from the HORIZON trials found significant reductions (vs. placebo) in the risk of any clinical fracture (35 %), clinical vertebral fractures (66 %), and nonvertebral fractures (27 %) in postmenopausal women aged ≥75 years [16].…”
Section: Discussionmentioning
confidence: 99%